Korean language e-learning for beginners / Nur Atiqah Idris - Idris, Nur Atiqah (2023)
E-learning is transitioning from traditional education or training to a more individualized and flexible education system based on information and communication technology. The people were considering that nowadays, the whole world is still dealing with the COVID-19 pandemic, which makes people unable to go anywhere as usual because of their safety. This project aims to develop Korean language e-learning (KLEB) using the VARK learning style model. VARK Learning is an educational technique that focuses on learning styles in a unique environment resulting in an exciting and dynamic learning environment where learners use ideas and have fun with the subject. With this, KLEB students can learn Korean anytime, anywhere. The development process will derive from the adapted ADDIE model. The adapted ADDIE model is a guide to creating practical designs widely used in the course design profession. This model provides methods for learning designers and content developers using adapted ADDIE model procedures to build efficient and successful learning designs. Currently, available courseware will be analyzed to gather important information about current features available. New features that do not exist in current software, such as animations to assist in pronunciation guidance with sound, and more, will be incorporated. Hopefully, the courseware will fulfil that objective and perhaps catalyze something bigger and better in the future.